1988
DOI: 10.1093/sleep/11.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Heat Exposure on Sleep Stages in Humans

Abstract: Six young men were exposed to a thermoneutral environment of air temperature (Ta) 20 degrees C for 5 days and nights followed by an acclimation period of 5 days and nights at Ta 35 degrees C and 2 recovery days and nights at Ta 20 degrees C. Electrophysiological measures of sleep, esophageal temperature, and mean skin temperature were continuously monitored. The total nocturnal body weight loss was measured by a sensitive platform scale. Compared with the 5 nights of the baseline period at 20 degrees C, sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0
3

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 16 publications
2
36
0
3
Order By: Relevance
“…It is possible that thermal load is increased in summer, since increased wakefulness is a typical effect of heat-exposure conditions (Karacan et al 1978;Haskell et al 1981;Libert et al 1988). Wakefulness may be the only stage that can manage the increased thermal load, given that thermoregulation is less active during sleep than in wakefulness (Parmeggiani 1987).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that thermal load is increased in summer, since increased wakefulness is a typical effect of heat-exposure conditions (Karacan et al 1978;Haskell et al 1981;Libert et al 1988). Wakefulness may be the only stage that can manage the increased thermal load, given that thermoregulation is less active during sleep than in wakefulness (Parmeggiani 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of REM sleep during summer remained almost at the basal level. The effect of acute exposure to warm ambient temperature on sleep has been studied extensively on human volunteers in controlled laboratory conditions (Karacan et al 1978;Muzet et al 1983;Libert et al 1988;OkamotoMizuno et al 1999;Okamoto-Mizuno et al 2004). These studies indicated that TST, stages 1 and 2, stages 3 and 4 and REM sleep decreased, with frequent and longer awakenings, greater shifting among sleep stages, and delayed onset of deep sleep (stages 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…INDIVIDUALS EXPOSED TO A THERMAL LOAD BEFORE 8,9,23,29,30,32,47 OR DURING 6,13,25,33,35,38,39,46 BED-TIME present alterations in their nocturnal sleep. Several adverse effects, which are known to reduce the subsequent vigilance level, have been determined, such as partial sleep deprivation and/or sleep fragmentation.…”
Section: Introductionmentioning
confidence: 99%